Evaluación de tilapia del Nilo (Oreochromis niloticus) y tilapia roja (O. sp) cultivadas en jaulas a 200, 400 y 600 peces por m3 en Zamorano, Comayagua y La Venta, Honduras - Gómez Z., Luís E.; Gutiérrez N., Bill H. (Zamorano: Escuela Agrícola Panamericana, 2016., 2016)
Gómez, L; Gutiérrez, B. 2008. Evaluation of tilapia of the Nile (Oreochromis niloticus) and red tilapia (O. sp.) cultured in cages at 200, 400 and 600 fish per m³ in Zamorano, Comayagua and La Venta, Honduras. Graduation project (Tessis) for the B. S. in Agriculture Science and Production, Pan-American School of Agriculture, Zamorano, Honduras. 18 p. A total of 13,500 fish were distributed in 27 cylindrical cages each of 1.25 m3 and made of 6 mm Vexar plastic netting (HDPE). The experiment was organized as a completely random design (DCA) with a factorial arangement 2 × 3 × 3 (two genetic lines of tilapia × three stocking densities × three localities). Each treatment had three replicates at each locality. All fish were fed a commercial tilapia feed three times per day for 63 days. Every 21 days the fish in each cage were counted and weighed in groups. All water quality parameters (temperature, dissolved oxygen, pH, transparency, total phosphorus and nitrogen) for the three localities were within the acceptable levels for tilapia culture. The best overall survival (P ≤ 0.05) of fish (combining red and Nile tilapia and the three stocking densities) was observed in Comayagua, followed by Zamorano and La Venta. An indirect relation between the stocking density and fish survival was observed in Comayagua, but not in Zamorano nor in La Venta. The greatest final average weights, combining red and Nile tilapia and the three stocking densities, was attained by the fish in La Venta and Comayagua. The fish managed in Zamorano had a significantly lower final average weight. There was no significant difference between red and Nile tilapia and their final average weights and total biomass increase per cage, stocked at three densities and in three localities. The greatest increase in fish biomass/cage was observed in Comayagua, followed by La Venta and Zamorano.